2021
DOI: 10.3390/ijms22168822
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Role of Phosphoglycerate Kinase 1 in Balloon Angioplasty-Induced Neointima Formation

Abstract: Restenosis is a common vascular complication after balloon angioplasty. Catheter balloon inflation-induced transient ischemia (hypoxia) of local arterial tissues plays a pathological role in neointima formation. Phosphoglycerate kinase 1 (PGK1), an adenosine triphosphate (ATP)-generating glycolytic enzyme, has been reported to associate with cell survival and can be triggered under hypoxia. The purposes of this study were to investigate the possible role and regulation of PGK1 in vascular smooth muscle cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The activity of phosphoglycerate kinase 1 (PGK1), a glycolytic enzyme, is associated with cell survival under hypoxia. As a result of PTA-induced arterial wall injury, PGK1 expression has been shown to increase, and the inhibition of PGK1 activity inhibits VSMCs migration and proliferation, leading to the suppression of neointima formation [101].…”
Section: Ischemia-reperfusion Injury In the Arterial Wall Associated With Ptamentioning
confidence: 99%
“…The activity of phosphoglycerate kinase 1 (PGK1), a glycolytic enzyme, is associated with cell survival under hypoxia. As a result of PTA-induced arterial wall injury, PGK1 expression has been shown to increase, and the inhibition of PGK1 activity inhibits VSMCs migration and proliferation, leading to the suppression of neointima formation [101].…”
Section: Ischemia-reperfusion Injury In the Arterial Wall Associated With Ptamentioning
confidence: 99%
“…Available drugs able to interfere with platelet aggregation are associated with increased risk of hemorrhage, warranting the development of effective, yet safer, anti-platelet drugs. The work by Barrachina et al has identified a compound, called Idelalisib, which potently inhibits platelet adhesion and aggregation by blocking Phosphoinositide 3-kinases (PI3K), but shows minimal bleeding effects in mice, compared to standard anti-platelet therapy, such as aspirin and clopidogrel, in mouse models [ 5 , 6 ].…”
mentioning
confidence: 99%
“…Recurrence of arterial stenosis (restenosis) after percutaneous transluminal coronary angioplasty (PTCA) is a frequent maladaptive response, occurring in up to 50% of patients, often requiring target vessel revascularization at one year, and associated with increased morbidity, mortality and health care costs. Pan and colleagues add a piece of evidence on the pathogenesis of the disease and provide novel insight into the role of phosphoglycerate kinase 1 (PGK1) in the regulation of vascular smooth muscle cell proliferation and neointima formation in hypoxic conditions [ 6 ]. Using both primary cell cultures and a rat carotid artery injury model, they showed that PGK1 is rapidly induced early after balloon angioplasty and that its inhibition effectively reduced neointima formation, thus providing evidence that a short-term intervention targeting early response genes could be as effective in preventing restenosis as long-term drug release [ 6 ].…”
mentioning
confidence: 99%